2014
DOI: 10.1038/srep07473
|View full text |Cite
|
Sign up to set email alerts
|

Eggshell membrane ameliorates hepatic fibrogenesis in human C3A cells and rats through changes in PPARγ-Endothelin 1 signaling

Abstract: Our previous nutrigenomic findings indicate that eggshell membrane (ESM) may prevent liver fibrosis. Here we investigated the effects and mechanisms underlying ESM intervention against liver injury by using DNA microarray analysis and comparative proteomics. In vitro hydrolyzed ESM attenuated the TGFβ1-induced procollagen production of human hepatocyte C3A cells and inhibited the expression of Endothelin 1 (EDN1) and its two receptors, and extracellular matrix components. In vivo male Wistar rats were allocate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…(Jiaa et al, 2013). These outcomes were in accordance with Jia et al, (2014) who found that dietary ESM displayed potential impacts on hepatic damage and fibrosis induced by CCl4 in rats.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…(Jiaa et al, 2013). These outcomes were in accordance with Jia et al, (2014) who found that dietary ESM displayed potential impacts on hepatic damage and fibrosis induced by CCl4 in rats.…”
Section: Discussionsupporting
confidence: 88%
“…Kim and Yoon, (2008) proposed that supplementation with chitosan oligosaccharide organization was compelling in the avoidance and change of the lipid level, lowering plasma cholesterol and chemical exercises in serum of hypercholesterolemic rats. Jiaa et al,(2013) and Jia et al, (2014) who indicating that ESM is a sheltered and common side-effect of egg preparing which has intense defensive biochemical capacities against liver damage and fibrosis. ESM may have a cholesterol cutting down effect that can cover liver harm, and at last liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The hepatic proteome analysis was conducted as described 8 in Supplemental Methods . A cut-off for p -values < 1.0 and confidence thresholds >1.25 were included for the identification of unique proteins using the IPA classification system.…”
Section: Methodsmentioning
confidence: 99%
“…We previously obtained nutrigenomic information from in vivo and in vitro investigations of ESM, and we observed biochemical functions of ESM that counter liver injury and fibrosis. These protective effects of ESM appear to be based on the regulation of proteins and genes that are related to the activation of hepatic stellate cells and fibrogenesis, via a potential novel modulation of the PPARγ-endothelin 1 interaction signaling pathway 8 .…”
mentioning
confidence: 99%
“…At the end of the 5-week experimental period, after 12 h of starvation, all rats were anesthetized with intraperitoneal chloral hydrate (300–350 mg/kg) at the same time of the day to avoid circadian metabolic fluctuations. Blood samples were obtained from the carotid artery and centrifuged immediately at 800 × g for 15 min at −4°C to separate the serum samples (Jia et al, 2014 ). All study procedures performed on the animals were approved by the Animal Care and Use Ethics Committees of China Agricultural University, and all rats received humane care in accordance with the guidelines.…”
Section: Methodsmentioning
confidence: 99%